Tax Avoidance and Corporate Social Responsibility: A Bibliometric Review and Future Agenda - Jeewanthi, H. A. C (NCC Journal, 2023)
This review explores the intellectual structure, research trends, and nexus within tax avoidance (TA) and corporate social responsibility (CSR) literature using the bibliometric research approach. Seventy-five peer-reviewed journal articles published between 2003 and 2022 in 56 journals were identified for the final analysis from Scopus databases. The articles were analysed and visualised with VOSviewer based on the keyword occurrence, authors, countries, and journal distribution. Even though 75 articles were identified on the interplay between CSR and tax avoidance, over sixty percent of papers were published during the last four years from only five countries. It indicates that combined CSR and tax avoidance research is emerging and has recently become a critical concern of scholarly investigation. Although the number of publications is increasing, author and country network analyses do not show a strong connection among authors and countries of publications. While the publications have been dispersed within a broader range of sources, only five journals are dominant, with three or more articles. Considering co-occurrence analysis, corporate social responsibility (CSR) and Tax avoidance are the frequently occurring terms within the publications, and they have been explored with other related areas such as corporate responsibility and sustainability, tax evasion, business ethics, corporate governance, tax havens, and earning management. Although keyword analysis shows that CSR and tax avoidance literature have been extensively studied during the past decade, this area of research is still in its infancy. Hence, more empirical research is needed from both developed and developing countries. Accordingly, this study provides exciting findings on the knowledge structures and patterns of tax avoidance and CSR research and valuable insights for future studies.